Pengaruh Struktur Aset dan Stabilitas Pendapatan terhadap Struktur Modal di BPRS PNM Mentari Garut - Syalsabila Raikhan Aulia; Widya Sari (Ma'soem University, 2022)
Based on the observation, that the background of this research is the fluctuating asset structure and income stability at BPRS PNM Mentari garut for the 2017 - 2021 period, thus causing fluctuations in the capital structure of the bank.This study aims to find out how the influence of asset structure and income stability on capital structure in BPRS PNM Mentari Garut period 2017 - 2021 either partially or simultaneously.The object of research in this report is to measure the capital structure. As for this type of research is quantitative associative with secondary data types with data collection techniques in the form of observation, interviews, documentation and literature study. The population in this study are all published financial reports of BPRS PNM Mentari Garut. The sampling technique was carried out by non-probability sampling, so that a sample was obtained, namely the quarterly financial statements for the period 2017-2021. The results showed that there was an influence between the asset structure on the capital structure at BPRS PNM Mentari Garut with the results of the t-test, namely the value of tcount > ttable (3, 02 > 1.73406). However, there is no significant effect between income stability and capital structure in BPRS PNM Mentari Garut, with the results of the t test, namely tcount < ttable (-0.776 < 1.73406). While, simultaneously the asset structure and income stability in BPRS PNM Mentari Garut affect the capital structure. This is indicated by the value of Fcount > Ftable (12.2 > 3.59.)